2017
DOI: 10.1016/j.celrep.2017.09.065
|View full text |Cite
|
Sign up to set email alerts
|

A Specific ChREBP and PPARα Cross-Talk Is Required for the Glucose-Mediated FGF21 Response

Abstract: SummaryWhile the physiological benefits of the fibroblast growth factor 21 (FGF21) hepatokine are documented in response to fasting, little information is available on Fgf21 regulation in a glucose-overload context. We report that peroxisome-proliferator-activated receptor α (PPARα), a nuclear receptor of the fasting response, is required with the carbohydrate-sensitive transcription factor carbohydrate-responsive element-binding protein (ChREBP) to balance FGF21 glucose response. Microarray analysis indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
90
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(94 citation statements)
references
References 49 publications
2
90
2
Order By: Relevance
“…Thus, it is likely that hepatic ChREBP in the mouse model reported by Jois et al is not fully ablated. This may explain why canonical ChREBP transcriptional targets were largely unaffected in their putative liver knockouts, in contrast with the data presented here and the data generated by multiple independent labs using global ChREBP-KO mice, which indicate that ChREBP is required for basal expression of many of its metabolic gene targets in vivo (8,11,17,38). Nevertheless, the results of Jois et al are interesting and suggest that different ChREBP isoforms may have distinct physiological and pathophysiological functions.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Thus, it is likely that hepatic ChREBP in the mouse model reported by Jois et al is not fully ablated. This may explain why canonical ChREBP transcriptional targets were largely unaffected in their putative liver knockouts, in contrast with the data presented here and the data generated by multiple independent labs using global ChREBP-KO mice, which indicate that ChREBP is required for basal expression of many of its metabolic gene targets in vivo (8,11,17,38). Nevertheless, the results of Jois et al are interesting and suggest that different ChREBP isoforms may have distinct physiological and pathophysiological functions.…”
Section: Discussioncontrasting
confidence: 85%
“…We and others have shown that hepatic ChREBP is particularly responsive to fructose consumption and that fructose-mediated activation of ChREBP may contribute to hepatic steatosis, hypertriglyceridemia, and both hepatic and peripheral insulin resistance (10)(11)(12). Recent data indicate that sugaror fructose-mediated activation of ChREBP also regulates secretion of hepatokines like FGF21, which contribute to adaptive metabolic responses to sugar consumption, including regulation of macronutrient preference and progression of NAFLD (13)(14)(15)(16)(17). Confirming the importance of ChREBP to fructose metabolism, whole-body ChREBP-knockout (ChREBP-KO) mice are intolerant to diets containing fructose and become moribund within 1 to 2 weeks (8).…”
Section: Introductionmentioning
confidence: 99%
“…Using the carbohydrate-responsive element-binding protein (ChREBP) −/− and PPAR-α knockout mice, it has been shown that PPAR-α cross-talks with ChREBP, a glucose-sensing lipogenic transcription factor, to regulate fibroblast growth factor (FGF)21 expression. The latter is a hepatokine that improves insulin sensitivity and lipid metabolism and controls the preference for sucrose [24,26]. Sterol regulatory element-binding protein (SREBP)1, which is the insulin-sensing variant of ChREBP, is apart from the liver X receptor, which is also regulated by PPAR-α.…”
Section: Introductionmentioning
confidence: 99%
“…Using PPAR-δ knockout mice, it could be demonstrated that PPAR-δ exhibits anti-atherogenic properties by reducing very-low density lipoproteins (VLDLs). This is also a consequence from FGF21 signaling [29], which also forms a link to PPAR-α [24,26]. PPAR-δ activation counters angiotensin II-induced adipocyte growth and lipid accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…We have showed recently that a hepatocyte-specific deletion of Ppar induces spontaneous steatosis in aging mice and blunts fasting-induced ketogenesis [18,19]. Moreover PPAR is required for the expression of fibroblast growth factor 21 (FGF21) [42,43], a liver-derived hormone with many endocrine [44] and hepatoprotective effects [45,46].…”
Section: Introductionmentioning
confidence: 99%